A perspectiva pluriativa como estratégia de reprodução da agricultura familiar na microrregião do agreste de Itabaiana-SE - Teixeira, Maria Cristina Santos (2017)
The end of 90’s in Brazil was dominated by economic, political and social changes affecting the dynamics of the rural area and also agriculture’s organization and production. This period was one of considerable development to the family-based agriculture, strengthened by the governmental recognition of a social class and also by redirecting of public policies for the rural setting. Brazilian agriculture went through a difficult path until its establishment as a social class, it also had a major role in society and continues fulfilling a substantial social role to this date. In the same decade, the debate about pluriactivity arose and gained notoriety from the Projeto Rurbano, which identified non-agricultural activities as the greater percentage between people engaged in the Brazilian rural environment. Understood here as pluriactivity is the family unit in which at least one of its members works in agricultural activities combined with another non-agricultural activity. The pluriactivity emerged as an alternative to stimulate family-based agriculture, a process that occurs in a natural way along societies, mostly in areas where farmers prove entrepreneurial capacity, besides easiness to adapt themselves to adverse situations, they have great power of flexibilization. This work aims to analyze the pluriactivity in the family-based agriculture as a social and economic reproduction strategy of families units located at the wild lands of Itabaiana-SE and its socio-spatial impacts. In order to reach the larger objective proposed in this research, specific objectives were achieved in the way allowing the formulation of this work as a whole. The theoretical and methodological procedures were bibliographic search, essential to the literature development and review, collection of sensitive data at public departments in digital platforms such as Instituto Brasileiro de Geografia e Estatística (IBGE), Instituto Nacional de Colonização e Reforma Agrária (INCRA), Ministério de Desenvolvimento Agrícola (MDA), Instituto de Pesquisa Econômica Aplicada (IPEA), and Censo Agropecuário. The field research was done directly (family-based farmers) and randomly using the sampling method along with a survey applied in villages that belong to the micro region. The major concern was to search for evidences which in turn would allow an analysis of how important is this pluriactivity to the family-based agriculture besides validate the family reproduction importance. The pluriactivity is fundamental in the life of the farmers, enabling improvement in the quality of rural life besides fixing the land, has been shown to be a strategy to combat rural poverty. Since income from non-agricultural activities in rural areas contributes to the maintenance of the family as well as to the acquisition of tools and inputs that are directly invested in agriculture and family ownership. In the face of the rural poverty framework, farmers over time have been enhancing their knowledge and skills and transforming them into profitable activities that could be incorporated into the dynamics of the family as secondary activities. As for the role of the State, there has not yet been an institutionalization of pluriactivity, only when the public power recognizes pluriactivity as a driver of development will it be possible to formulate and implement public policies of valorization of the farmer. From the discursions of the literature and also based on secondary data, it can be concluded that the Microregion of Agreste of Itabaiana presents the existence of pluriactivity and its importance for the promotion of local rural development.